STRATEGI INDUSTRIALISASI UNGGULAN DALAM PEMBANGUNAN WILAYAH: SUATU PENDEKATAN ANALITIS (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to analyze the structure of leading industrialization in regional development, by identifying factors that influence the growth of the industrial sector and its contribution to economic development. Using a qualitative descriptive approach based on literature studies and policy analysis, this article highlights the importance of mapping leading sectors to strengthen regional competitiveness amidst global economic dynamics. The results of the analysis show that the success of leading industrialization is largely determined by the availability of resources, government policies, infrastructure, quality of the workforce, and technology adoption. A targeted and collaborative industrialization strategy between government, industry, and society is the key to accelerating regional economic growth in a sustainable manner.